The Legal Challenges of Protecting the Electronic Consumer in Social Commerce in Iraq - Dr. Mahmood Shaker Abood (Indonesian Journal of Law and Economics Review, 2026)
General Background: The rapid expansion of social media–based commercial activities has transformed digital trade, positioning social commerce as an increasingly significant component of contemporary electronic commerce systems. Specific Background: In Iraq, the growing use of social media platforms for online transactions has created new opportunities for business activities while simultaneously exposing electronic consumers to risks associated with indirect transactions, limited transparency, and potential fraud. Knowledge Gap: Despite the development of social commerce practices, the existing Iraqi legal framework does not adequately address the specific regulatory requirements of electronic consumer protection, particularly in relation to misleading advertisements, pre-contractual information disclosure, unfair contractual terms, and the evidentiary validity of electronic contracts. Aims: This study aims to examine the legal challenges surrounding the protection of electronic consumers in Iraqi social commerce by analyzing current legislation and identifying regulatory deficiencies. Results: Using a descriptive–analytical legal approach based on Iraqi consumer protection and electronic transaction laws, the study identifies significant legislative shortcomings, including weak regulation of electronic advertising, insufficient mechanisms for verifying electronic contracts, and the non-activation of the electronic signature system due to the absence of a national certification authority. Novelty: The research provides a structured legal analysis linking consumer protection stages pre-contractual, contractual, and post-contractual to the specific regulatory deficiencies within Iraq’s social commerce environment. Implications: The findings indicate the necessity of legislative reform, stronger regulatory oversight, activation of electronic transaction laws, and the establishment of institutional mechanisms to secure electronic consumer rights and strengthen trust in Iraq’s digital marketplace. Highlights:• Identifies Major Legislative Gaps in Iraqi Regulation of Social Commerce Transactions.• Reveals Risks Related to Misleading Digital Advertising and Unverifiable Online Contracts.• Recommends Activation of Electronic Signature Law and Creation of Certification Authority. Keywords: Consumer Protection, Social Commerce, Electronic Commerce Law, Electronic Consumer Rights, Iraqi Legal Framework.